2014
DOI: 10.1128/jvi.01945-14
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphorylated-STAT1 Nuclear Translocation and Antiviral Protein Expression in Human Brain Vascular Adventitial Fibroblasts Infected with Varicella-Zoster Virus

Abstract: In varicella-zoster virus (VZV)-infected primary human brain vascular adventitial fibroblasts (BRAFs), levels of beta interferon (IFN-␤V aricella-zoster virus (VZV) vasculopathy is often protracted, perhaps due in part to persistent infection of arterial adventitial fibroblasts (1). A potential mechanism of virus persistence is evasion of the antiviral type I interferon (interferon alpha [IFN-␣] and IFN-␤) response (2) which induces antiviral interferon-inducible genes such as Mx1. Mx1 belongs to the dynamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
2
8
1
Order By: Relevance
“…Although HCMV and vaccinia virus infection block phosphorylation of STAT1 via the induction of cellular or viral tyrosine phosphatase expression [24,25], we showed that SVVinduced inhibition of IFNg-induced STAT1 phosphorylation did not involve active dephosphorylation by phosphatases. Our data suggest that SVV infection does not induce degradation of STAT1 protein, suggesting that the virus may reduce STAT1 mRNA expression levels, as was recently demonstrated for VZV [29]. Moreover, we demonstrate that SVV utilizes distinct mechanisms to reduce STAT1 protein levels and block IFNg-induced phosphorylation of STAT1.…”
Section: Vaccinia Virus and Hcmv Antagonize Ifng-induced Stat1 Phosphsupporting
confidence: 82%
See 1 more Smart Citation
“…Although HCMV and vaccinia virus infection block phosphorylation of STAT1 via the induction of cellular or viral tyrosine phosphatase expression [24,25], we showed that SVVinduced inhibition of IFNg-induced STAT1 phosphorylation did not involve active dephosphorylation by phosphatases. Our data suggest that SVV infection does not induce degradation of STAT1 protein, suggesting that the virus may reduce STAT1 mRNA expression levels, as was recently demonstrated for VZV [29]. Moreover, we demonstrate that SVV utilizes distinct mechanisms to reduce STAT1 protein levels and block IFNg-induced phosphorylation of STAT1.…”
Section: Vaccinia Virus and Hcmv Antagonize Ifng-induced Stat1 Phosphsupporting
confidence: 82%
“…STAT1 is shared between the IFN-a/b and IFNg signalling pathways, thereby providing an ideal target for immune evasion [12]. Similarly, previous studies reported that VZVthe human homologue of SVVreduced STAT1 protein levels in infected human foreskin fibroblasts and brain-derived vascular adventitial fibroblasts [18,29]. Interestingly, others did not detect SVV-or VZV-induced reduction of STAT1 protein level in rhesus macaque and human lung fibroblasts [27], possibly due to a cell-type specific effect.…”
Section: Vaccinia Virus and Hcmv Antagonize Ifng-induced Stat1 Phosphmentioning
confidence: 92%
“…At the time of CPE, conditioned supernatant and cell lysates were prepared as described [8] from VZV- and mock-infected BRAFs, and analyzed for levels of MMP-1, -2, -3 and -9 protein by a multiple immunoassay (Meso Scale Discovery, Rockville, MD) according to the manufacturer’s directions. Each MMP was quantitated (ng/mL) using a standard curve, and the fold change determined for VZV-infected and mock-infected conditioned supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all conceivable mechanisms of inhibition have been realized by herpesviruses (see Table ): (I) loss of IFN receptor or their signaling capability [both shown for KSHV ], (II) loss of janus kinases or their enzymatic activity [shown for EBV ], (III) loss of certain STAT molecules , their interaction partner IRF‐9 [shown for HCMV ], their nuclear translocation [shown for HSV and VZV ] or their transcriptional activity , (IV) inhibition of signaling by the expression of viral IRF homologues [shown for KSHV ], (V) block of ISG induction by a global host‐shut‐off [as shown for α‐herpesviruses ] and (VI) upregulation of cell‐intrinsic negative feed‐back regulatory proteins [e.g. PIAS or SOCS proteins – as shown for EBV ].…”
Section: Herpesviral Inhibitors Of Ifn Signalingmentioning
confidence: 99%